PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PT. UNILEVER INDONESIA, TBK PERIODE TAHUN 1998-2011 - Mulyani, Sri (2013)
Consumer goods industry is one of the major industrial sectors in Indonesia. In this decade, the consumer goods industry has developed rapidly, but amid these developments, some of the consumer goods sector firms showed unfavorable performance indications, as happened in PT. Unilever Indonesia, Tbk. The research was motivated by the declining value of the DPR PT. Unilever Indonesia, Tbk. And Find a picture of liquidity as measured by the current ratio (CR), Leverage as meansured by the debt to ratio at PT Unilever Indonesia, Tbk. As well as testing the effect of current ratio (CR) and debt to ratio (DR) of the dividend payout ratio (DPR). The research methods used in this research are descriptive and verification methods, with sampling using secondary data from the years 1998-2011. In the process of hypothesis testing, analysis tools used in this study including multiple regression, correlation, coefficient of determination, F test and t test. The results showed that partially, CR has a positive and significant impact on the DPR. while DR has no significant negative impact on the DPR. Simultaneously, the results of the F test statistic states that CR and DR have significant effect on the DPR.Coefficient of determinationis 80%while theremaining 20% areinfluenced byother variablesnot examinedin this study. Key words: Liquidity, Current Ratio, Leverage, Debt to Ratio, Dividend Policy, Dividend Payout Ratio